Insecticidal and antifeedant activity of Momordica charantia aqueous extract against cutworm, Spodoptera litura(f.) (lepidoptera: noctuidae) larvae - Nur Atiqah M.K.,; Chong, T.V.; Rozeita L., (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2015)
Antifeedant activity of aqueous extract of Momordica charantia (Cucurbitaceae) leaf or commonly known as ‘peria katak’ was tested on early 4th instar larvae of Spodoptera litura. The preliminary study was carried out to investigate the effect of feeding activity on body weight of S.litura. From the study, the early 4th larval instar was fed with fresh leaves of M. charantiaas well as fresh leaves of cabbage used as a control. The larvae fed on M. charantia leaves showed a high percentage value of reduction in weight, which is 91.81% after feeding at day-7. The aqueous extract of M. charantia was then prepared to determine the deterrent feeding activity of the larvae. The deterrent feeding activity is count based on percentage of starvation index (Percent starvation = (C-E) / (C-S) x 100; Where: C = Mean weight gain of control larvae within 24 hours, E = Mean weight gain of treated larvae at each tested concentration within 24 hours, S = Mean weight gain of starved control larvae within 24 hours). The 100% concentration of extracts was tested. From the experiment, the extract exhibited a significant antifeedant activity at the LC50 levels. We found that the extract of M. charantia has antifeedant activity against S. litura larvae, where 100% concentration gave 57.02% of starvation index.